Pelatihan dan Pendampingan Kelompok Mitra PKM di Desa Leseng, Kecamatan Moyo Hulu, Kabupaten Sumbawa - Heri Kusnayadi; Ana Merdekawati; Wening Kusumawardani (Institut Pertanian Bogor, 2019)
This activity was claimed to enhance the knowledge and skills of cultivation partner group (Uma Pelam) and processing group (Wanita Rumpi Sayang Keluarga). The training and mentoring were conducted from March to June 2018 in Leseng Village, Moyo Hulu Subdistrict, Sumbawa Regency. The aproach used was active participation method, training and mentoring with the target were partner groups. The result showed that there were 85% of partners had actively implemented the community partnership program. The cultivation group had been understood the technique of corn cultivation in dry land and corn drying technique by utilizing the sunlight as a heat source. The processing partner have had skills to process corn into corn brownies, corn dodol, and corn chips (Semarang corn). Both of them have understood the technique of book keeping and group bussiness management. The existence of partner group have been widely known by the people in sumbawa regency with the publication of community partnership program activities in mass media Gaung NTB and Online Media Indicator Inn.